The influence of proactive personality on students’ knowledge sharing: the chain mediating effect of class climate and learning engagement - Lin, Ye; Jin, Yongchao; Yang, Rui (Frontiers in Psychology, 2024)
IntroductionKnowledge sharing is an effective means of knowledge management in colleges and universities, which is of great significance for improving the quality and efficiency of universities and enhancing the balanced development of educational resources. The present study investigated the influence students’ proactive personalities drive knowledge-sharing activities, and examined the significance of class climate and learning engagement as mediating factors, utilizing the perspectives of social exchange theory (SET) and the job demands and resources model (JD-R) .MethodsA convenience sampling method was employed to survey 1,053 Chinese college students, and evaluated them using the Proactive Personality Scale (PPS), Learning Engagement Scale (LES), Class Climate Scale (CCS), and Knowledge Sharing Behavior Scale (KSBS). The structural equation model and bootstrap method to explore the significance of the mediating effect of class climate and learning engagement between proactive personality and knowledge sharing of college students.Results(1) Proactive personality was positively associated with students’ knowledge sharing behavior; (2) Class climate had a significant mediating effect between proactive personality and knowledge sharing behavior of college students, and the mediating effect of class climate is 21.2%; (3) Learning engagement mediated effect between proactive personality and knowledge sharing behavior, and the mediating effect ratio of learning engagement is 8.4%; (4) Class climate and learning engagement play a chain mediating role in the relationship between proactive personality and knowledge sharing behavior of students, and the chain mediating role accounted for 2.1% of the total effect.ConclusionProactive personality exerts a significant impact on students’ knowledge-sharing behaviors. However, this effect is not direct; it is mediated by both class climate and learning engagement. Specifically, students exhibiting higher levels of proactivity are more likely to actively engage in the learning process and foster a positive class climate, which, in turn, enhances their propensity to share knowledge with peers.